RECENT TENDENCIES IN PV/T SYSTEM PERFORMANCE – A REVIEW - TEODOR POP; RADU-DUMITRU PENTIUC; VISARION-CĂTĂLIN IFRIM; PAVEL ATĂNĂSOAE (Journal of Engineering Studies and Research)
The capacity, performance and ease of photovoltaic/thermal systems in producing at the same time electricity and heat have made this technology one of the most significant in terms of energy, worldwide. In the past years, researchers have focused their work on obtaining new configurations of hybrid PV/T systems that are sustainable, solve problems related to the space on the roof of buildings, lead to reduced emissions of greenhouse gases (GHG) and protect our natural environment by using renewable resources. This paper presents the recent trends of hybrid PV/T systems and their performance. Also, the thermal and electrical efficiencies are indicated for each studied article.